CONSTITUTIONAL AMENDMENT IN A DEMOCRATIC RULE OF LAW STATE IN INDONESIA - Suriadiata, Irpan (JILPR Journal Indonesia Law and Policy Review, 2024)
This research was conducted with the aim of finding out: 1) Procedures and practices for changing the constitution in Indonesia 2) Constitutional amendments in a democratic rule of law state in Indonesia. The type of research used in this research is normative legal research using a statutory approach and a conceptual approach. The types and sources of legal materials in this research are primary and secondary legal materials. The results of this research show that: 1) The procedures and practices for changing the constitution in Indonesia are regulated in several regulations, including: the 1945 Constitution to the RIS Constitution, the RIS Constitution to the 1950 Constitution, the 1950 UUDS to the 1945 Constitution and the 1945 Constitution (Decree) to the 1945 Constitution (Amendment). 2) Constitutional amendments in a democratic legal state in Indonesia, namely: First, changes to the constitution must be in accordance with procedures that have been determined by themselves, because this is what is in accordance with changes to the constitution according to law (vervassunganderung). Second, institutions that make changes must receive legitimacy from the people. Third, actions or changes to the constitution must involve the community.